2021
DOI: 10.1089/dna.2021.0056
|View full text |Cite
|
Sign up to set email alerts
|

SERPINB5 Genetic Variants rs2289519 and rs2289521 are Significantly Associated with Gallbladder Cancer Risk

Abstract: Serine protease inhibitor b5 (SERPINB5) is a tumor suppressor gene that plays a critical role in various cellular processes. In gallbladder cancer (GBC), SERPINB5's aberrant expression is reported but its role in genetic predisposition is not known. We enrolled 270 cases and 296 controls and genotyped them for single nucleotide polymorphisms (SNPs) using direct DNA sequencing, followed by genotype-phenotype analysis in GBC and other cancer cell lines. Luciferase assay was done to determine the role of rs228952… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The serpin family B member 5 (SERPINB5), located on chromosome 18q21.33 as a tumor suppressor gene, plays a critical in cancer cell invasion and metastasis. SERPINB5 variants are significantly associated with gallbladder cancer risk (43). Upregulated Maspin inhibited the expression of IKKα to promote cell apoptosis and delayed the development of the precancerous lesions in precancerous rats (44).…”
Section: Discussionmentioning
confidence: 99%
“…The serpin family B member 5 (SERPINB5), located on chromosome 18q21.33 as a tumor suppressor gene, plays a critical in cancer cell invasion and metastasis. SERPINB5 variants are significantly associated with gallbladder cancer risk (43). Upregulated Maspin inhibited the expression of IKKα to promote cell apoptosis and delayed the development of the precancerous lesions in precancerous rats (44).…”
Section: Discussionmentioning
confidence: 99%
“…29 It has been stated that SERPINB5 genetic variation is closely related to the occurrence of GBC. 30,31 Dong's research group reported that SERPINB5 reduces the accumulation of matrix metalloproteinases MMP2 and MMP9 to decelerate the migration and invasion processes of GBC cells. 32 However, the Snail.…”
Section: Studies Have Shown That Foxa2 Can Participate In Cancer Init...mentioning
confidence: 99%
“…22 Additionally, the homozygous maspin-S176 has been linked with gallbladder cancer. 23 However, how a minor variation in the unstructured region can drastically alter the function of an antitumor protein to protumor protein is still a mystery. Structural biology has advanced our understanding of the three-dimensional structures of different proteins; however, the lack of a dynamic picture of these proteins hinders their functional aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Maspin-P176, in conjunction with maspin-L187, decreases the risk of esophageal squamous cell carcinoma, whereas maspin-S176 (with maspin-V187) exerts the opposite effect . Additionally, the homozygous maspin-S176 has been linked with gallbladder cancer . However, how a minor variation in the unstructured region can drastically alter the function of an antitumor protein to protumor protein is still a mystery.…”
Section: Introductionmentioning
confidence: 99%